Genetic Complexity of Sinoatrial Node Dysfunction - Wallace, Michael J.; El Refaey, Mona; Mesirca, Pietro; Hund, Thomas J.; Mangoni, Matteo E.; Mohler, Peter J. (Frontiers in Genetics, 2021)
The pacemaker cells of the cardiac sinoatrial node (SAN) are essential for normal cardiac automaticity. Dysfunction in cardiac pacemaking results in human sinoatrial node dysfunction (SND). SND more generally occurs in the elderly population and is associated with impaired pacemaker function causing abnormal heart rhythm. Individuals with SND have a variety of symptoms including sinus bradycardia, sinus arrest, SAN block, bradycardia/tachycardia syndrome, and syncope. Importantly, individuals with SND report chronotropic incompetence in response to stress and/or exercise. SND may be genetic or secondary to systemic or cardiovascular conditions. Current management of patients with SND is limited to the relief of arrhythmia symptoms and pacemaker implantation if indicated. Lack of effective therapeutic measures that target the underlying causes of SND renders management of these patients challenging due to its progressive nature and has highlighted a critical need to improve our understanding of its underlying mechanistic basis of SND. This review focuses on current information on the genetics underlying SND, followed by future implications of this knowledge in the management of individuals with SND.